Dampak Kebijakan Subsidi Pertanian Terhadap Produktivitas Petani di Kota Tebing Tinggi Sumatera - Saad Fitrah Auliya; Apip Gunaldi Dalimunthe (MES Bogor, 2025)
This study aims to analyze the effect of agricultural subsidy policies on farmer productivity in Tebing Tinggi City, Sumatra. The method used is simple linear regression with independent variables of agricultural subsidy policies and dependent variables of farmer productivity. The research sample was 370 respondents determined using the Slovin formula. Data were collected through a google form survey and analyzed using SPSS 25. The results showed that agricultural subsidy policies have a positive and significant effect on farmer productivity with a regression coefficient of 0.865 and a significance level of 0.000. The Beta value of 0.930 indicates that subsidy policies have a very strong impact on increasing farmer productivity. These findings indicate that agricultural subsidies can be an important instrument in improving farmer welfare and supporting food security in the area. Therefore, a more optimal and sustainable subsidy policy is needed to increase the productivity of the agricultural sector in Tebing Tinggi City.